VIDEO ANALYSIS, SURPRISE AFTER RETURNING HOME, AS A PUBLIC SPHERE TO FULFILL FAMILY FOOD NEEDS ON THE INSTAGRAM ACCOUNT @BU_UTIQ - Tina Kartika; Dr. Nanang Trenggono; Dr. Nina Yudha Aryanti; Dr. Abdul Firman Ashaf; Prof.Andy Corry Wardhani (Faculty of Social and Political Sciences, Universitas Lampung, 2025)
Video Analysis, Surprise after returning home, as a public sphere to fulfill family food needs on the Instagram account @bu_utiq. This study's use of video as social media material on the Instagram account @bu_utiq illustrates how social media may serve as a forum for public discourse and information gathering. Instagram is one of the social media that can influence the audience to change their behavior. The narrative of Mrs.Utiq and her family returning from their hometown and discovering a surprise—36 chicken eggs in their chicken coop—is told in the video material titled Surprise after returning home. @Ibu_Utiq's chicken farming activities for efforts to meet daily food needs. This study was conducted using the netnography method on video content uploads entitled Surprise after retuning home. The videos analyzed were the top 30 comments, with content analysis, captions and comments. The stages of netnography analysis in this study with the Kozinets analysis guide are through initiation, identification, interaction, and immersion. After four days of being left at home, 36 eggs were found with 16 active laying hens and 4 hens incubating them, according to the video material on the Instagram account @bu_utiq on April 3, 2025. This indicates that the chickens have a 75% probability of successfully producing eggs. As a result, it demonstrates a high degree of success in laying hen production. This produces gardening and livestock-related content that goes viral on social media, garnering enormous attention with each upload receiving hundreds of thousands to millions of likes and thousands of comments. Findings Instagram account @bu_utiq also presents educational, innovative, and inspiring content for its viewers. This includes tips and tricks for caring for chickens and their cages to keep them healthy and clean, educational advice and informative messages that are very educational. This video becomes a public discussion, with reciprocal comments so that this content becomes an interesting discussion space.